2023
DOI: 10.1108/scm-06-2022-0219
|View full text |Cite
|
Sign up to set email alerts
|

Highlight risk management in supply chain finance: effects of supply chain risk management capabilities on financing performance of small-medium enterprises

Abstract: Purpose The purpose of this paper is to explore the important role of supply chain risk management (SCRM) capabilities as pre-factors for SMEs to improve supply chain financing performance (SCFP), also incorporating the effect of supply chain integration (SCI). Design/methodology/approach From the intersection of SCRM and SCF literature, this paper proposed hypothesis to discuss the impact of SCRM capabilities on SCFP and the role of SCI, aiming at combine SCRM with supply chain financing management. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In addition, risk is an important topic in supply chain finance. Qiao et al [3] found that supply chain risk management has a significant impact on the performance of supply chain finance via the study of data obtained from 286 SMEs. Li, Y. et al [4] used a hybrid extreme gradient boosting multilayer perceptron (XGBoost-MLP) model to assess the credit risk of digital SCF.…”
Section: Literature Review 21 Supply Chain Finance and Risk Measureme...mentioning
confidence: 99%
“…In addition, risk is an important topic in supply chain finance. Qiao et al [3] found that supply chain risk management has a significant impact on the performance of supply chain finance via the study of data obtained from 286 SMEs. Li, Y. et al [4] used a hybrid extreme gradient boosting multilayer perceptron (XGBoost-MLP) model to assess the credit risk of digital SCF.…”
Section: Literature Review 21 Supply Chain Finance and Risk Measureme...mentioning
confidence: 99%
“…When enterprises apply the tool of supply chain finance, it becomes extremely important to fully consider their internal circumstances. Through effective risk control and management [36], they can better promote sustainable growth and ensure their long-term financial stability and market competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In reality, FSPs can be financial institutions or supply chain focus enterprises; they are not limited to a specific type of entity (Song et al, 2018). Existing literature has mainly focused on the operation mode Lu et al, 2022b;Yan and Sun, 2015), risk management and control (Xu et al, 2018), information technology application (Lu et al, 2020;Song et al, 2021), network structure (Jhang et al, 2021;Steven et al, 2019), innovation capabilities (Lu et al, 2020;Fabbri and Klapper, 2016;Qiao and Zhao, 2023), supply chain collaboration (Pfohl and Gomm, 2009), the overall operation efficiency of the supply chain (Filbeck et al, 2016) and other aspects of supply chain finance (Beka Be Nguema et al, 2021b;Elliot et al, 2020). From these perspectives, scholars have conducted a significant amount of research on the driving factors of SCFP, as seen in Table 1.…”
Section: Supply Chain Financingmentioning
confidence: 99%